Exploring Clinical and Echocardiographic Factors in EHRA Type 2 Atrial Fibrillation for Predicting Ischaemic Stroke: A Search for Unrevealed Insights - Simbolon, Jessica Putri Natalia; Raharjo, Sunu Budhi; Santoso, Anwar; Liastuti, Lies Dina; Hermanto, Dony Yugo; Rossimaria, Vienna; Pritazahra, Armalya; Hanafy, Dicky Armein; Yuniadi, Yoga (The Indonesian Heart Association, 2023)
Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia in adults. Valvular heart diseases (VHD), regardless of the arrhythmic problems, increase the risk of thromboembolism, which are even higher in those with associated atrial fibrillation. The EHRA (Evaluated Heartvalves, Rheumatic or Artificial) classification categorised AF patients with significant VHD into type 1 and type 2. Unfortunately, there are currently very limited data on risk prediction in stroke-related valvular AF, particularly in the Asian population. Aims: To investigate the clinical and echocardiographic risk factors for ischaemic stroke prediction in patients with EHRA type 2 VHD. Methods: This retrospective study enrolled 695 AF patients with EHRA type 2 VHD. The data were collected from patients' medical records who met the inclusion and exclusion criteria from 2015 until 2020. The primary outcome was ischaemic strokes within observation period. Results: There were 67 ischaemic stroke events (9,6%) of the total sample. Our analysis found that none of the analysed variables proved to be statistically significant risk factors in predicting the occurrence of ischaemic stroke. The median CHA2DS2-VASc risk prediction in the sample was 3, with an accuracy of AUC 0.502 (CI 95%; 0.429 – 0.576), sensitivity 56.7% and specificity 44.7%. Conclusion: Based on the parameters analysed in this study, no factor was statistically well-predictive to predict the ischaemic stroke incidence in EHRA type 2 VHD AF. In addition, the CHA2DS2-VAS accuracy was low in this population. Further exploration is needed to build an accurate ischaemic stroke risk prediction for EHRA type 2 VHD.This article has a related Erratum.